On the variance of the number of real roots of a random trigonometric polynomial. (1990) - Farahmand, K.
Abstract : This paper provides an upper estimate for the variance of the number of real zeros of the random trigonometric polynomial g 1 cos θ + g 2 cos 2 θ + … + g n cos n θ . The coefficients g i ( i = 1, 2, …, n ) are assumed independent and normally distributed with mean zero and variance one.